The Influence of YouTube Electronic Word of Mouth and Service Quality on Customer Satisfaction - Rizal Fahmi; Nurjamilah Nurjamilah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Indonesia is an archipelagic country with abundant natural and cultural resources that support the development of the tourism sector. Bandung is one of Indonesia’s leading tourist destinations, supported by travel service providers such as Fast Travel Sentosa. This study aims to analyze the condition of Electronic Word of Mouth (eWOM) on YouTube, service quality, and customer satisfaction at Fast Travel Sentosa Bandung. This research uses a quantitative approach with descriptive and verificative methods. Data were collected through questionnaires distributed to customers and analyzed using statistical methods. The results show that Electronic Word of Mouth and service quality have a significant relationship and simultaneously influence customer satisfaction at Fast Travel Sentosa Bandung. These findings are expected to provide strategic input for improving service quality and digital communication, as well as to enrich scientific references in the field of digital marketing and travel service management.